Review on Rare Itemset Mining - Ninoria, SZ; Thakur, SS (International Journal of Computer Sciences and Engineering, 2025)
These Data mining is the procedure of analyzing unseen patterns of data according to different point of view for classification into useful information, which is collected and gathered in common areas, such as data warehouses, for proficient investigation, data mining algorithms, assisting business decision making and other information requirements to eventually cut costs and raise profits. Data mining is also recognized as data discovery and knowledge discovery. Frequent itemset mining is a significant task in data mining to discover the hidden, interesting associations between items in the database based on the userspecified support and confidence thresholds. Patterns detected by the Association Rule Mining technique are highly useful patterns as are playing vital role in decision making. In this paper we have focused on the other side of the ARM technique which should also get equal emphasis while decision making as the patterns which are not frequent can be more valuable as those are the Rare Itemsets. The fundamental technique of finding the frequent patterns can be used reversely for Rare Itemset Mining. In this paper the brief study of the technique available for Rare Itemset Mining is discussed and explored the utility of the Rare Itemsets in the decision making.